Manierysta w nowoczesności - Rabizo-Birek, Magdalena (Tematy i Konteksty, 2015)
In the review main interpretation theses of Andrzej Niewiadomski’s monograph devoted to the writing of the outstanding emigration author from ‘the generation 1910’ Zygmunt Haupt have been presented. These are: the aesthetics of mannerism, critical diagnosis of modernity crowned with an attempt to build a constructive ethical and literary project and a thorough analysis of the key motives of his prose (including aviarium, art of mannerism, theatrum mundi, road-home, a landowner’s manor house, horses, word ‘strange’, ‘quaternary’ structures).The author presents writer’s workshop secrets and places him among the greatest representatives of Polish as well as European modernism.